Determination of damage length in aluminum 2024 T-3 plate by lamb wave - ÜNAL, MUHAMMET (PAMUKKALE UNIV, 2017)
In this study, cuts between 2 and 5 cm formed on Aluminum 2024 T-3 plate for damage detection and structural health monitoring were examined with Lamb waves and the symmetric and asymmetric modes of Lamb waves were compared. The envelopes of the acquired surface frequency responses are obtained by Hilbert transform and the amount of attenuation of each damage is shown as a percentage. The results show that both Lamb wave modes can be used to investigate the cut dimensions created in the Aluminum 2024 T-3 plate.
Keywords: Lamb wave; Hilbert transform; structural health monitoring; WAFER ACTIVE SENSORS; LOCALIZATION; EXCITATION; SIGNALS